The Adoption of Indirect Instruments of Monetary Policy - Balino, Tomas (Occasional Papers; Occasional Paper ;, 1995)
This paper examines the experience of implementing indirect instruments of monetary policy. The experiences of country studies illustrate the variety of circumstances under which indirect instruments of monetary policy have been introduced. Case Studies are presented for Chile, Egypt, Ghana, Indonesia, Mexico, New Zealand, and Poland.